Description of Clean and Healthy Behavior Program Implementation at School During COVID-19 Pandemic at Depok City Health Office in 2021 - Hadiah Ardiani (CV. Ridwan Publisher, 2023)
COVID-19 pandemic has had an impact on social activities, one of which is teaching and learning activities in schools. This research aims to discuss an overview of the implementation carried out by the Depok City Health Office in order to increase the coverage of School PHBS during the COVID-19 pandemic in 2021.This preliminary study is a qualitative research with a descriptive approach.The data collection process was carried out using in-depth interviews and document review methods. This research shows that the implementation of the PHBS program in school settings is carried out through health human resources who adapt to teamwork mechanisms, available facilities and infrastructure, budgets and technical instructions that go through an adaptation process during the COVID-19 pandemic as well as the dynamics of school activities based on existing regulations. applies in Depok City related to learning activities in schools. The obstacles experienced include limited facilities in schools and the process of implementing online monitoring and coaching activities has resulted in a gap in response in several schools implementing the PHBS program.The implementation of the PHBS program for schools during the COVID-19 pandemic at the Depok City Health Office, which was reviewed through the structure, implementation process and applicable regulations, experienced several obstacles in online activities and supporting facilities that had not been fulfilled. However, the indicators for the PHBS program in school settings can be implemented through various adaptations of the activities that have been carried out.